Analysis of Relations between Essential Oils and Diseases by Using Association Rules - Ozpolat, Zeynep; Yildirim, Gokce; Tanyildizi, Erkan (Ieee, 2018)
From the oldest known civilizations to the presented plants are used in the field of health and beauty. Aromatherapy is used to alleviate the symptoms of many diseases and physical and psychological treatment to help. Essential oils can be appleid by inhalation, or rubbing into the skin for diseases. In this study, the relationship between certain disease their effects are examined with essential oils of these oils. Data set used in the application of different diseases consists of 70 units and 100 units used in the treatment of these diseases aromatherapy oil plant. These relations of association rules algorithms using one of Apriori algorithm are studied to determine. As a result of experimental studies, used for one or more plant diseases, some results may be used for a different disease is obtained.
Uçucu Ya?lar ile Etki Ettikleri Hastaliklar Arasindaki Ilişkilerin Birliktelik Kurali ile Analizi
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Data Mining; Association Rules; Aromatherapy; Essential oils